Hungarian Monitoring, 5 September 1988 . [Magyar rádiófigyelő], 1988. szeptember 5 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Cardinal Glemp travels to Moscow - Chief of Soviet general staff's letter to Pravda - Demonstration held without permission in Moscow - Polish trade unions against Solidarity Domestic Affairs: - Károly Grósz's speech at the Political College year opening ceremony - Shamir receives state secretary Imre Miklós in Jerusalem - "Népszabadság" newspaper (People's Freedom) forum in Pécs - Last day of three-day environmental protection conference - Social discussion of draft bill on right to assemble and associate - Chances of Vienna-Budapest World Exposition - Democratic Trade Union of Academics position criticizing inflation Külpolitika: - Glemp bíboros moszkvai útja - A szovjet vezérkari főnök cikke a Pravdában - Engedély nélküli felvonulás Moszkvában - A lengyel szakszervezetek a Szolidaritás ellen Belpolitika: - Grósz Károly beszéde a Politikai Főiskola tanévnyitóján - Samír Jeruzsálemben fogadja Miklós Imre államtitkárt - Pécsi Népszabadság fórum - A három napos környezetvédelmi konferencia utolsó napja - Társadalmi vita a gyülekezési és egyesülési jog törvénytervezetéről - A Bécs - Budapest világkiállítás esélye - A TDDSZ inflációt kritizáló állásfoglalása